2000
DOI: 10.1002/(sici)1097-4628(20000516)76:7<1186::aid-app22>3.0.co;2-n
|View full text |Cite
|
Sign up to set email alerts
|

Seeded emulsion polymerization of styrene: influence of acrylic acid on the particle growth process

Abstract: ABSTRACT:The seeded batch emulsion copolymerization of styrene and acrylic acid was studied. The polymerization rate was investigated with pH as the main parameter. Some attempts were made to evaluate the average number of growing chains per particle during Stage II of the emulsion polymerization process. The final latex products were characterized by means of conductometric aqueous titration and potentiometric titration in an organic solvent mixture. The distribution of the acid groups over the aqueous phase,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
27
0

Year Published

2000
2000
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 28 publications
3
27
0
Order By: Relevance
“…At low pH values the AA is rather hydrophobic and at pH values above 5.5 AA is deprotonated and more hydrophilic (pK a of AA corresponds to 4.25). [28] Bearing in mind that the quantity of carboxylic groups on the particle's surface is very high, the ionic interactions might influence the coverage of the surface with BSA. As it was mentioned above, at pH ¼ 3, the adsorbed amount of BSA is higher than at pH ¼ 6 due to the stronger interaction between the anionic particle's surface and positive charges of BSA molecules.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…At low pH values the AA is rather hydrophobic and at pH values above 5.5 AA is deprotonated and more hydrophilic (pK a of AA corresponds to 4.25). [28] Bearing in mind that the quantity of carboxylic groups on the particle's surface is very high, the ionic interactions might influence the coverage of the surface with BSA. As it was mentioned above, at pH ¼ 3, the adsorbed amount of BSA is higher than at pH ¼ 6 due to the stronger interaction between the anionic particle's surface and positive charges of BSA molecules.…”
Section: Isothermal Titration Calorimetrymentioning
confidence: 99%
“…In this study, two methods were used for determining the carboxylic group's distribution: conductometry to evaluate the number of carboxylic groups on the surface of the latex particles, and titration with NaOH in methanol solution to determine the number of carboxylic groups inside and on the surface of the latex particles. 1,8,14,15 The concentration of carboxylic groups in the serum (water phase) was determined by centrifugation and conductometric titration by means of a mass balance, i.e., deduced from the initial amount of carboxylic monomer introduced and the determined amounts of carboxylic groups inside and at the surface of the latex particles. The number of carboxylic groups on the particle surface was determined by titration of a cleaned latex solution against a 0.05 N NaOH.…”
Section: Carboxylic Group Distributionmentioning
confidence: 99%
“…Hence, the participation of propagation in aqueous phase and its effect on R p could be neglected. 3,5,6 So R p is calculated from eq 3.…”
Section: Determination Of Polymerization Ratmentioning
confidence: 99%
“…polymerization rate per particle or equivalently average number of propagating radicals per particle is also affected by the presences of carboxylic acid monomers. 3,[5][6][7][8] Shoaf and Poehlein 7,8 developed a model that describes the kinetics of particle growth in seeded emulsion copolymerization of styrene with acrylic and methacrylic acids. These authors confirmed the influence of events taking place in the aqueous phase on the basic mechanisms operating in the particle growth stage.…”
mentioning
confidence: 99%
See 1 more Smart Citation